Determinants of Work Stress on Elementary School Teachers during Implementation of Hybrid System at COVID-19 Pandemic: A Case Study of Cilacap and Tuban Indonesian District - Lusi Ismayenti; Isna Tasya Salsabilla; Syafrina Ossawanda; Tutug Bolet Atmojo; Maria Paskanita Widjanarti (Nusantara Science and Technology Proceedings, 2022)
The COVID-19 pandemic is impacting health but also education. The impact is online learning. After the condition of the coronavirus has decreased globally, WHO made a policy regarding the new normal. In Indonesia, the impact of this policy is the learning system through offline and online methods (hybrid learning). Students learn at home and school alternately. The teacher makes various preparations, selects learning tools, and innovates so that students have an interest in learning, are not bored, and succeed. The addition of teachers' tasks and responsibilities resulted in work stress. This study aims to determinants of work stress for elementary school teachers during the implementation of a hybrid system during the COVID-19 pandemic: a case study of Cilacap and Tuban districts. A cross-sectional study was performed on 124 respondents. Age, gender, and working period using a self-data questionnaire, mental workload using NASA-TLX, and work stress using the HSE 2003 questionnaire. Spearman tests were performed to correlate age, gender, working period, and mental workload with work stress. There was a significant correlation between age (p=0.001), working period (p=0.002), mental workload (p=0.001), and work stress. Gender (p=0.690) did not correlate with work stress. Based on the results of studies that have been carried out, factors that correlate with work stress are age, working period, and mental workload. The factors that do not correlate with work stress are gender. Teachers are recommended to adapt to a hybrid learning system.